2020
DOI: 10.3390/cells9092101
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Cellular Autophagy and Hepatitis B Virus Replication: A Systematic Review

Abstract: Autophagy, a conserved process in which cells break down and destroy old, damaged, or abnormal proteins and other substances in the cytoplasm through lysosomal degradation, occurs via autophagosome formation and aids in the maintenance of intracellular homeostasis. Autophagy is closely associated with hepatitis B virus (HBV) replication and assembly. Currently, HBV infection is still one of the most serious public health issues worldwide. The unavailability of satisfactory therapeutic strategies for chronic HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 88 publications
0
37
0
Order By: Relevance
“…Guo et al showed that treatment of HBVexpressing HepG2.2.15 cells with high concentrations of inhibitors of PI3K, Akt, and mTOR (10, 5, and 10 lmol/L, respectively) increased the transcription of 3.5-kb and 2.4kb viral RNA as well as the replication of HBV DNA (Guo et al 2007b). However, some other studies including ours showed that low concentrations (B 1 lmol/L) of the inhibitors significantly enhanced HBV replication through enhancing autophagy instead of HBV transcription (Huang et al 2014;Lin et al 2020). There are many binding sites of ubiquitous and hepatocyte-enriched transcription factors in the promoter and enhancer regions of the HBV genome, including that for the transcription factors PGC1a and the PPARa/retinoid X receptor alpha (RXRa) complex.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Guo et al showed that treatment of HBVexpressing HepG2.2.15 cells with high concentrations of inhibitors of PI3K, Akt, and mTOR (10, 5, and 10 lmol/L, respectively) increased the transcription of 3.5-kb and 2.4kb viral RNA as well as the replication of HBV DNA (Guo et al 2007b). However, some other studies including ours showed that low concentrations (B 1 lmol/L) of the inhibitors significantly enhanced HBV replication through enhancing autophagy instead of HBV transcription (Huang et al 2014;Lin et al 2020). There are many binding sites of ubiquitous and hepatocyte-enriched transcription factors in the promoter and enhancer regions of the HBV genome, including that for the transcription factors PGC1a and the PPARa/retinoid X receptor alpha (RXRa) complex.…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with these findings, HBsAg expression in chronic hepatitis B is significantly upregulated compared with that in HBV-associated HCC (Wang M et al 2013), which has a higher PI3K/Akt activity. However, low inhibitor concentrations of PI3K, Akt and mTOR mainly modulate posttranscriptional steps of HBV life cycle (Lin et al 2020). The roles of HBV in the mTOR signaling pathway are summarized in Fig.…”
Section: Hbv-mediated Activation Of Mtor Signaling Pathwaymentioning
confidence: 99%
“…Depending on the type of virus, autophagy can either benefit or hinder virus replication. For instance, hepatitis B virus and dengue virus facilitate their replication and maturation by enhancing autophagy ( Jordan and Randall, 2017 ; Lin et al, 2020 ). In contrast, autophagy induction by starvation or pharmacological inhibitors blocks ASFV infection in vitro ( Hernaez et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some viruses, such as human cytomegalovirus, coxsackievirus B3, and herpes simplex virus type 1, inhibit autophagy [27][28][29]. Conversely, other viruses, such as hepatitis B virus, human immunodeficiency virus, dengue virus, and influenza virus, facilitate their replication and maturation by enhancing the autophagy [30][31][32][33][34]. The interaction between different CoV infections and autophagy has recently attracted a lot of attention.…”
Section: Autophagymentioning
confidence: 99%